2021
DOI: 10.1155/2021/6082506
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Work-Related Musculoskeletal Disorders and Associated Factors among Restaurant Workers in Gondar City, Northwest Ethiopia, 2020

Abstract: Introduction. Globally, work-related musculoskeletal disorders (WMSDs) have resulted in occupational disability and injury. Of these, restaurant workers are among the high-risk professionals usually affected by WMSDs. In Ethiopia, evidence on the burden of musculoskeletal disorder and contributing factors among restaurant workers were very limited. Therefore, this study was aimed at assessing the prevalence of self-reported WMSDs and contributing factors among restaurant workers in Gondar city, northwest Ethio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 36 publications
3
18
2
1
Order By: Relevance
“…Low back disorders (LBDs) were by far the most common (SL incidence) work-related MSDs in both gender and age groups ( Figure 1 ). This finding is consistent with the results of previous studies, reporting that workers in the hotel [ 15 , 16 ] and restaurant [ 17 , 18 ] industries suffered mainly from low back pain. Although the most commonly affected body region was the low back, the hip, including osteoarthritis and other cartilage disorders ( Table 1 ), was associated with the longest mean SL duration.…”
Section: Discussionsupporting
confidence: 93%
“…Low back disorders (LBDs) were by far the most common (SL incidence) work-related MSDs in both gender and age groups ( Figure 1 ). This finding is consistent with the results of previous studies, reporting that workers in the hotel [ 15 , 16 ] and restaurant [ 17 , 18 ] industries suffered mainly from low back pain. Although the most commonly affected body region was the low back, the hip, including osteoarthritis and other cartilage disorders ( Table 1 ), was associated with the longest mean SL duration.…”
Section: Discussionsupporting
confidence: 93%
“…Tegenu [ 11 ], in 2021, in another cross-sectional study of 633 catering workers, showed that 81.5% of workers had musculoskeletal disorders and that the upper back, elbow and wrist were the most affected parts.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, behavioral/lifestyle, like cigarette smoking, alcohol use, BMI, and physical activities [ 5 , 31 ] are significant factors. Most conspicuously, extensive investigations have shown that psychosocial factors such as job stress [ 32 – 34 ], job satisfaction [ 28 , 35 ], and job demand [ 31 ] are among the key causes of WRUEDs. Whereas, working hours [ 36 ], working posture [ 30 , 37 ], rest breaks taken, and safety training [ 38 ] are among workplace determinants in the manifestation of WRUEDs.…”
Section: Introductionmentioning
confidence: 99%